Combination of verteporfin photodynamic therapy and ranibizumab: effects on retinal anatomy, choroidal perfusion and visual function in the protect study. Issue 12 (24th November 2008) - Kiss, C G; Simader, C; Michels, S; Schmidt-Erfurth, U
Abstract : Objective: To evaluate verteporfin and same-day ranibizumab on retina, choroid, vasculature, choroidal neovascularisation (CNV) and visual function. Methods: Eleven patients with occult or predominantly classic subfoveal CNV secondary to age-related macular degeneration received verteporfin and four monthly intravitreal ranibizumab injections. Eyes were examined using fluorescein angiography (FA) and indocyanine green angiography (ICGA), optical coherence tomography (OCT), visual acuity (VA) and microperimetry. Results: Over 9 months, seven patients gained three to 24 letters and one had unchanged VA. Three patients lost eight to 24 letters due to recurrence and received another verteporfin treatment at month 6. Median retinal sensitivity of the central 4° of the macula increased from 0.9 (SD 2.3) dB (baseline) to 5.2 (1.8) dB (only baseline verteporfin) and 4.1 (4.5) dB (second verteporfin treatment) at study end. OCT showed sub- and intraretinal leakage increased with verteporfin, but resolved after 2 weeks. After combination treatment, CNV was completely occluded on FA within 1 week. ICGA showed non-perfusion of small/medium choroidal vessels. Recovery of choroidal perfusion began after 1 month, but remained impaired throughout follow-up. Conclusion: Verteporfin/ranibizumab was associated with CNV occlusion, reduced oedema, improved visual function and retinal sensitivity. The clinical significance of these findings requires further investigation.